Revised recommendations on standards and norms for palliative care in Europe from the European Association for Palliative Care (EAPC): A Delphi study. (April 2022) - Payne, Sheila; Harding, Andrew; Williams, Tom; Ling, Julie; Ostgathe, Christoph
Background: In 2009, the EAPC published recommendations on standards and norms for palliative care in Europe, and a decade later, wished to update them to reflect contemporary practice. Aim: To elicit consensus on standards and norms for palliative care in Europe, taking account of developments since 2009. Design: A Delphi technique used three sequential online survey rounds, and a final expert consultation (EAPC Board). The original 2009 questionnaire with 134 statements was updated with 13 new concepts and practices following a scoping of the literature between 2009 and 2020 (total: 147 statements). Setting/participants: One contact of Boards of 52 national European organisations affiliated to the EAPC were invited to participate, with subsequent rounds sent to respondees. The EAPC Board ( n = 13) approved final recommendations. Results: In Round 1: 30 organisations (14 organisations × two people, 16 organisations × one person, total n = 44) in 27 countries responded (response rate 58% organisations, 82% countries), Round 2 ( n = 40), Round 3 ( n = 38). 119 statements reached consensus in Round 1, 9 in Round 2, 7 in Round 3. In total 135/145 statements in five domains (terminology, philosophy, levels, delivery, services) reached consensus (defined as >75% agreement), (122) were original EAPC recommendations with 13 new recommendations included emerging specialisms: neonatal, geriatric and dementia care, and better care practices. Seven statements failed to reach consensus and four were removed as irrelevant or repetition. Conclusions: Most recommendations on standards and norms for palliative care in Europe remain unchanged since 2009. Evolving concepts in palliative care can be used to support advocacy.